KENYAMANAN TEMPAT KERJA PUSTAKAWAN: PERSPEKTIF ERGONOMI - endang fadmawati (Pustakaloka, 2014)
Factors considered on  the work are  the work environment, hardware, and cooperation between the computer’s users. An  increase on  productivity  is  a  librarian  purpose.  However,  work  in  the  office (library)  can  also  have  an  impact  that  is not  good  for  the  safety  and health librarians. So it is necessary to know how safe and well in the use of work equipment in the library in order to avoid accidents and other health problems. In short, ergonomics  is the study of human behavior related to his job.